Grammaire cognitive des prépositions : épistémologie et applications - Jean-Rémi Lapaire (Corela)
Cognitive Grammar first began as « space grammar » so it is no coincidence that spatial cognition should have played a major role in the development of the general theoretical framework. Terms referring to spatial concepts such as domain, region, space, stage, zone, frame, ground, landmark are still used extensively to describe a wide range of linguistic phenomena, extending beyond spatial organization.Prepositions are primarily viewed as spatial grams whose basic schematic meanings have been extended to other domains. As such, prepositions reveal the construal operations that underlie the semiotic expression of spatial configurations. They are also sure indicators of conceptual transfer processes. Prepositions are typically ascribed an abstract configurational structure that is usually represented in diagrammatic form. Precious insight is thus provided into the contentfulness and meaningfulness of grammatical morphemes, the patterned nature and imagistic quality of grammatical meaning, the ecology and experiential grounding of human conceptualization strategies, the interplay between notional and functional motivations in grammaticalization processes.